2021
DOI: 10.3390/molecules26195972
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, It’s Regulation and Antiphlogistic Effect of the Cyanogenic Glycoside Amygdalin

Abstract: The inflammatory reaction accompanies in part or in full any disease process in the vascularized metazoan. This complicated reaction is controlled by regulatory mechanisms, some of which produce unpleasant symptomatic manifestations of inflammation. Therefore, there has been an effort to develop selective drugs aimed at removing pain, fever, or swelling. Gradually, however, serious adverse side effects of such inhibitors became apparent. Scientific research has therefore continued to explore new possibilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 185 publications
(212 reference statements)
0
11
0
Order By: Relevance
“…Cytokines includes interleukins (IL), chemokines, interferons, and tumor necrosis factors (TNF) ( 57 ). Inflammatory mediators, include proteins, peptides, glycoproteins, cytokines (TNF), prostaglandins, leukotrienes, nitric oxide, and oxygen free radicals ( 58 ). Hydrogels, such as the PVA/AH hydrogel mentioned in the study, have shown promise in generating anti-inflammatory effects by modulating the production of pro-inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines includes interleukins (IL), chemokines, interferons, and tumor necrosis factors (TNF) ( 57 ). Inflammatory mediators, include proteins, peptides, glycoproteins, cytokines (TNF), prostaglandins, leukotrienes, nitric oxide, and oxygen free radicals ( 58 ). Hydrogels, such as the PVA/AH hydrogel mentioned in the study, have shown promise in generating anti-inflammatory effects by modulating the production of pro-inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a great need and urgency to discover novel drugs for IBD [ 33 ]. Amygdalin (Amy) exerts anti-inflammatory and antioxidant effects in multiple diseases [ 34 ]. In the present study, Amy administration alleviated colitis symptoms (as manifested by decreased weight loss, increased colon length, and reduced DAI scores) and colonic tissue damage in mice with colitis by suppressing DSS-induced colonic inflammatory responses, oxidative stress, and epithelial cell death as well as rebalancing intestinal flora, demonstrating that Amy may serve as a preventive and therapeutic agent for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a biological defense response in the vascularized tissues of multicellular organisms to a stimulus such as a foreign pathogen or internal tissue damage 32 . The anti-inflammatory activity evaluation was carried out on on male albino rats (Rattus novergicus).…”
Section: Anti-inflammatorymentioning
confidence: 99%